ҲӘЗИРГИ ЗАМАН БИЛИМЛЕНДИРИЎИНДЕГИ СҮЎРЕТЛЕЎ ӨНЕРИНИҢ РОЛИ - Уразимова, Т.В. (ILIM hám JÁMIYET, 2025)
The article is devoted to the issues of the role of fine arts in the system of modern education. In this regard, we pay attention to global changes in the modern system of education and the role of fine arts in the general process of development. In addition, fine arts are considered by us as one of the main means of educating a modern harmonious personality, a comprehensively developed person, educated, progressive, highly moral, with the ability to work, a desire to create and understanding the beauty of life.